Synthesis and Characterization of Ni-Ti Partially Substituted Hexaferrites for High-Density Magnetic Recording Applications - Ibrahim Bsoul; Suaad Assrhan; Sami H. Mahmood (Jordan Journal of Physics, 2025)
Executive AbstractM-type hexaferrite (AFe12O19; A = Ba2+, Sr2+, Pb2+) is an important magnetic oxide exhibitingmagnetic properties suitable for a wide range of technological and industrial applications. The magnetic properties of M-type hexaferrite can be tuned for a specific application by adopting suitable synthesis routes and/or using special cationic substitutions for either Fe3+or A2+cations. In particular,coercive fields in the range of 1 – 3 kOe and remnant magnetization > 20 emu/g are required for data storage media in high-density magnetic recording applications. Partial substitution of Fe3+ions by Co2+-Ti4+ ions in BaM (BaFe12O19) or SrM (SrFe12O19) hexaferrite was long recognized as an effective procedure for reducing the coercivity to values appropriate for high- density magnetic recording, without decreasing the remnant magnetization appreciably. Also, the effects of other substitutions were extensively investigated. However, the M-type hexaferrite with Ni2+-Ti4+ substitution was generally ignored, especially when compared with the extensively investigated Co2+-Ti4+ substituted system. This work was motivated by the potential of Ni-Ti substitution to reduce the coercivity of SrM hexaferrite to appropriate levels and maintain the remnant magnetization high enough for high-density magnetic recording applications. . . . . Keywords: Hexaferrites, Partial substitution, Nickel, Titanium, High-density magnetic recording.